Increasing incidence of lentigo maligna and lentigo maligna melanoma in Catalonia. (13th December 2018) - Matas‐Nadal, Clara; Malvehy, Josep; Ferreres, Jose Ramon; Boada, Aram; Bodet, Domingo; Segura, Sonia; Salleras, Montse; Azon, Antoni; Bel‐Pla, Susana; Bigata, Xavier; Campoy, Antoni; Curcó, Neus; et al.
Abstract: Background: Recent epidemiological studies suggest that past data where superficial spreading melanoma was by far the most common subtype of melanoma may not reflect current patterns of sun exposure or other risk factors more involved in other subtypes of melanoma as lentigo maligna (LM) or lentigo maligna melanoma (LMM). Methods: In order to measure the current situation in our country, all cases of LM and LMM diagnosed in 23 hospitals in Catalonia, from 2000 to 2007, were recorded. Results: Although for the global period LM/LMM represented only 8.4% of cases, an increasing trend in this percentage was observed throughout the study period (from 6.9% [27 cases] in 2000 to 13.1% [94 cases] in 2007). Also, an increasing incidence of LM/LMM was observed, especially in chronically sun‐exposed areas (85.5% involving the head and neck region). During the 8 years of the registry, the mean Breslow thickness of LMM remained stable. However, the increase in the number of LM ( in situ ) cases was significantly higher than the increase of the invasive ones. Conclusions: An important observation from this data is that aging of population and current sun exposure patterns could keep increasing the incidence of LM/LMM, which may become an important public healthcare problem, over the other histological subtypes. In order to establish primary or secondary preventive measures to the LM/LMM risk‐population, it is imperative to highlight the importance of chronic sun damage as a melanoma risk factor, and not only sunburn, most commonly addressed in melanoma prevention campaigns.